Microstructure Evolution of Al-Mn-Si-Fe Alloy Studied by In-situ Transmission Electron Microscopy - Pokova, Michaela; Cieslar, Miroslav (Manufacturing Technology Journal, 2014)
Equal channel angular pressing is one of the techniques of severe plastic deformation, which produce materials with sub-micrometric grains. Materials with grains under 1 μm are of great importance for industrial applications thanks to enhanced strength at lower temperatures and formability at elevated temperatures. One of the possible ways how to enhance microstructure stability of aluminium alloys at elevates temperatures is addition of small amount of zirconium. In our study, heat treatment at 450 °C leads to precipitation of Al3Zr phase. After ECAP these particles postpone recrystallization above 400 °C. However, in the material without Al3Zr particles the recrystallization resistance is comparable thanks to impact of α-Al(Mn,Fe)Si phases. More over, initial microhardness after ECAP is higher for the alloy, which was not heat-treated at 450 °C before ECAP, thanks to higher dislocation density and solid solution strengthening by Mn atoms.
Keywords: Aluminium alloys; ECAP; TEM; recrystallization; precipitation